Angela carter’s heroes and villains: a dystopian romance - Zirange, Rajaram Sitaram (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The present paper modestly attempts to study Angela Carter’s Heroes and Villains (1969) as a dystopian romance in apocalyptic mode .It is an attempt to present how Angela Carter critically examines Rousseau’s Utopia of Noble Savage in Heroes and Villains. Carter juxtaposed Rousseau’s concept of ‘Noble Savage’ with the Barbarian Jewel, who does not represent natural ‘goodness of man’ and ‘perfectibility’ which are the merits attributed by Rousseau to his noble savage. Carter debunks the romantic idea of a ‘Noble Savage’ as well as an idyllic picture of the countryside, outside the walls of civilization. Carter scrutinizes Rousseau’s utopian idea of Noble Savage and also shows how the western Enlightenment concept of Binarism to establish identity of the privileged group is misleading as well as responsible for mistrust and harmful conflict between communities. Angela Carter combines dystopia with subversion of the genre of romance in Heroes and Villains. It encodes ‘female values’ of love and relatedness as well as ‘male aggressiveness’ and competition. The paper concludes that Angela Carter examines Rousseau’s utopian notion of Noble Savage as well as his notion of the ideal womanhood in Heroes and Villains. She has created a kind of laboratory world in which there are only three communities, the Professors, the Barbarians and the Savages. It is in this post-apocalyptic futurist world that she examines the utopian ideas of Rousseau. She subverts the romantic notion of love, courtship and manners that categorize popular romances.